Perception of men on the abortion process - Dantas, Larissa Correia Nunes; Diniz, Normélia Maria Freire; Couto, Telmara Menezes (Rev Rene, 2011)
This is a descriptive, qualitative study, carried out in a public maternity hospital in Salvador (BA). It aimed to analyze men’s perception of abortion. Four men, mates of women who had had abortions and been to the hospital as their mates were being discharged, were interviewed on January 2009. The semi-structured interview was used as a data collection instrument and was organized based on thematic analysis. The results were as follows: men see abortion as a crime, before God and before men. They knew misoprostol, although, they ignore this process and its consequences to women. The decision for abortion is up to women: men don’t take part in it. However, they express ambivalent feelings resulting on that experience, explaining this decision as a matter of financial problems. Welcoming elements are recommended to men and the implementation of public policies of healthy reproduction, in a sharing action between men and women.